2009
DOI: 10.1007/s11676-009-0002-6
|View full text |Cite
|
Sign up to set email alerts
|

Species diversity and regeneration of old-growth seasonally dry Shorea robusta forests following gap formation

Abstract: Diversity and regeneration of woody species were investigated in two ecological niches viz. gap and intact vegetation in old-growth seasonally dry Shorea robusta (Gaertn. f.) forests in Nepal. We also related varieties of diversity measures and regeneration attributes to gap characteristics. Stem density of tree and shrub components is higher in the gap than in the intact vegetation. Seedling densities of S. robusta and Terminalia alata (B. Heyne ex Roth.) are higher in the gap than in the intact vegetation, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 37 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…High canopy cover in ungrazed areas may be limiting regeneration of light dependent plants leading to overall low diversity of regenerants. High regeneration of light dependent plants was also observed in Nepal as result of forest gap effects [16]. [17] found that tree species richness was higher in the gap than in the intact vegetation in broad leaved forest in the southern China.…”
Section: Discussionmentioning
confidence: 86%
“…High canopy cover in ungrazed areas may be limiting regeneration of light dependent plants leading to overall low diversity of regenerants. High regeneration of light dependent plants was also observed in Nepal as result of forest gap effects [16]. [17] found that tree species richness was higher in the gap than in the intact vegetation in broad leaved forest in the southern China.…”
Section: Discussionmentioning
confidence: 86%
“…Shorea robusta has ability to re-sprout aggressively from root suckers after short duration of disturbances (Gautam and Devoe, 2006;Sapkota et al, 2009a). It has proved to be more aggressive than its competitors with its resistance to forest fires and other external factors through the die-back mechanism (Champion and Seth, 1968).…”
Section: Tree Layer Diversitymentioning
confidence: 99%
“…Previous studies have also shown that species distributions and seedling recruitment in tropical forests are related to topography, soil conditions, and light availability. For example, gaps are important in maintaining species diversity and regeneration in ancient or tropical and subtropical forests (Hubbell et al 1999;Sapkota et al 2009). In tropical forests, soil type and topography play an important role in shaping diversity, as both of these factors influence water and nutrient availability (Miyamoto et al 2003;Phillips et al 2003).…”
Section: Exploring Key Factors Affecting Regeneration Dynamics Along Various Environmental Axesmentioning
confidence: 99%